Imaging using radiolabelled targeted proteins: radioimmunodetection and beyond - Javad Garousi; Anna Orlova; Fredrik Y. Frejd; Vladimir Tolmachev (SpringerOpen, 2020)
Abstract The use of radiolabelled antibodies was proposed in 1970s for staging of malignant tumours. Intensive research established chemistry for radiolabelling of proteins and understanding of factors determining biodistribution and targeting properties. The use of radioimmunodetection for staging of cancer was not established as common practice due to approval and widespread use of [18F]-FDG, which provided a more general diagnostic use than antibodies or their fragments. Expanded application of antibody-based therapeutics renewed the interest in radiolabelled antibodies. RadioimmunoPET emerged as a powerful tool for evaluation of pharmacokinetics of and target engagement by biotherapeutics. In addition to monoclonal antibodies, new radiolabelled engineered proteins have recently appeared, offering high-contrast imaging of expression of therapeutic molecular targets in tumours shortly after injection. This creates preconditions for noninvasive determination of a target expression level and stratification of patients for targeted therapies. Radiolabelled proteins hold great promise to play an important role in development and implementation of personalised targeted treatment of malignant tumours. This article provides an overview of biodistribution and tumour-seeking features of major classes of targeting proteins currently utilized for molecular imaging. Such information might be useful for researchers entering the field of the protein-based radionuclide molecular imaging.